2008
DOI: 10.1111/j.1537-2995.2007.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Apheresis donors and platelet function: inherent platelet responsiveness influences platelet quality

Abstract: The most activated apheresis PLTs were obtained from donors with more responsive PLTs. Regular apheresis, however, does not lead to PLT activation in the donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…Unfortunately, it is unknown to which extent CD40L synthesis can also occur by this pathway, and if there is an influence of storage duration on it. However, it was shown that platelet activation and 'platelet storage lesion' are influenced by individual preconditions of the donors [35,36].…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, it is unknown to which extent CD40L synthesis can also occur by this pathway, and if there is an influence of storage duration on it. However, it was shown that platelet activation and 'platelet storage lesion' are influenced by individual preconditions of the donors [35,36].…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, it is not examined to which content CD40L synthesis can also occur by this pathway, and if there is an influence of storage duration on it. But it was shown that platelet activation and "platelet storage lesion" are influenced by individual preconditions of the donors [14,17] and that interactions with thromboxane can influence sCD40L expression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the range and consistence of interindividual variation in the PLT response [20], but little is known about the effect of apheresis on donors' PLTs. Today, platelet concentrates are generally produced from whole blood by differential centrifugation (pooled buffy coat-derived platelet concentrates -PCs) or by apheresis (apheresisderived platelet concentrates -APCs).…”
Section: Immature Platelets In Donors 55mentioning
confidence: 99%